Combined supplementation of leucine and glutamine acts as a novel therapeutic approach to alleviate hyperglycemia and oxidative stress by targeting insulin signalling genes in a drosophila model of type 2 diabetes. - Dash, K.; Mishra, M. (Molecular Biology Reports, 2025)
To evaluate the therapeutic potential of leucine and glutamine, individually and in combination, in alleviating metabolic dysfunction associated with Type 2 Diabetes (T2D) using a high sucrose diet-induced Drosophila model of T2D. T2D was induced in flies by feeding a high-sucrose diet (35%). Optimal nontoxic doses of leucine and glutamine were administered to T2D flies for seven days. The therapeutic effects were assessed in individual and combined doses through biochemical, histological, and molecular analyses. Combined leucine and glutamine supplementation demonstrated superior efficacy over individual treatments. Biochemical analysis revealed that supplementation alleviates hyperglycemia and hyperlipidemia. Improved oxidative stress markers are indicated by increased thiol levels, DPPH radical scavenging, antioxidant enzyme activity, decreased protein carbonylation, and lipid peroxidation. Histological assessment found less lipid droplet accumulation in the gut, reduced reactive oxygen species accumulation, restoration of actin filament architecture, and decreased apoptotic cell death in the gut and malpighian tubules. Efflux activity in malpighian tubules was significantly improved post-treatment. qPCR studies indicate that the combination therapy of Leucine and Glutamine predominantly targets downstream components of insulin signaling pathways, including chico and Akt, while secondarily stimulating insulin secretion, which typically diminishes in the later stages of chronic hyperglycemia. The elevation of cytoskeletal genes Actin 57B and Actin 88 F and elevated mRNA expression of sns and kirre, essential for nephrocyte-mediated hemolymph detoxification, underscores the multifaceted treatment strategy. The current study underscores the potential of leucine and glutamine co-supplementation as a promising intervention to mitigate metabolic dysregulation in T2D.